Reduced dynamic functional connectivity between salience and executive brain networks in insomnia disorder. (3rd December 2019) - Wei, Yishul; Leerssen, Jeanne; Wassing, Rick; Stoffers, Diederick; Perrier, Joy; Van Someren, Eus J. W.
Summary: Research into insomnia disorder has pointed to large‐scale brain network dysfunctions. Dynamic functional connectivity is instrumental to cognitive functions but has not been investigated in insomnia disorder. This study assessed between‐network functional connectivity strength and variability in patients with insomnia disorder as compared with matched controls without sleep complaints. Twelve‐minute resting‐state functional magnetic resonance images and T1‐weighed images were acquired in 65 people diagnosed with insomnia disorder (21–69 years, 48 female) and 65 matched controls without sleep complaints (22–70 years, 42 female). Pairwise correlations between the activity time series of 14 resting‐state networks and temporal variability of the correlations were compared between cases and controls. After false discovery rate correction for multiple comparisons, people with insomnia disorder and controls did not differ significantly in terms of mean between‐network functional connectivity strength; people with insomnia disorder did, however, show less functional connectivity variability between the anterior salience network and the left executive‐control network. The finding suggests less flexible interactions between the networks during the resting state in people with insomnia disorder.